Nominalization in Academic Writing: A Cross-disciplinary Investigation of Physics and Applied Linguistics Empirical Research Articles - Alireza Jalilifar; Zhila Heidari Kaidan; Alexanne Don (Iranian Journal of Applied Language Studies, 2018)
The present study aimed to explore how nominalization is manifested in a sample of Physics and Applied Linguistics research articles (RAs), representing hard and soft sciences respectively. To this end, 60 RAs from discipline-related professional journals were randomly selected and analyzed in light of Halliday and Matthiessen’s (1999) taxonomy of nominalization. Comparing the normalized frequencies indicated that articles in Applied Linguistics differ significantly from their counterparts in Physics as they include more nominalized expressions. Moreover, the analysis brought out the findings that deployment of nominalization Type Two is significantly different from the other three types of nominalization in each discipline. Subsequently, the obtained expressions were put into their context of use in order to extract the most prevalent patterns of nominalization in the RAs. The investigation into the embedded patterns introduced 15 common patterns for Physics and Applied Linguistics RAs. Chi-square analyses suggested statistically significant differences in using only four patterns. Finally, implications accrue to the findings in reference to academic writing teachers and course designers.